2013
DOI: 10.1021/jp3093379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Bonding on Internal Conversion of GFP-like Chromophores. I. The para-Amino Systems

Abstract: To understand the effects of solvent-solute hydrogen bonding (SSHB) on the excited-state dynamics of two GFP-like chromophores, p-ABDI and p-CFABDI, we have determined the quantum yields for fluorescence (Φf) and the isomerization Z → E (ΦZE) and the femtosecond fluorescence and transient infrared absorption in selected solvents. The behavior that ΦZE ≅ 0.50 in aprotic solvents, such as CH3CN, indicates that the E-Z photoisomerization adopts a one-bond-flip mechanism through the torsion of the exocyclic C═C bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 48 publications
5
55
0
Order By: Relevance
“…Moreover, the probability of finding electrons at imidazolinone ring is negligible in the HOMO, but is significant in the LUMO. The enhanced charge-transfer character entails a reduction in S 1 →S 0 emission [20] which is supported by the short fluorescence lifetimes for all complexes [34]. From the HOMO delocalization we can infer that the enhanced charge transfer occurs during the deexcitation process and the extra electron density on phenol ring will attracts a proton since it is positively charged.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Moreover, the probability of finding electrons at imidazolinone ring is negligible in the HOMO, but is significant in the LUMO. The enhanced charge-transfer character entails a reduction in S 1 →S 0 emission [20] which is supported by the short fluorescence lifetimes for all complexes [34]. From the HOMO delocalization we can infer that the enhanced charge transfer occurs during the deexcitation process and the extra electron density on phenol ring will attracts a proton since it is positively charged.…”
Section: Resultsmentioning
confidence: 63%
“…Significant charge transfer character within the chromophore implies large changes in molecular electron density which triggers the non-radiative decay by transition between anionic and neutral form. This is supported by the increase of λ abs for 2His-EGFP-Cu 2+ at 395 nm which means that the push−pull electronic character of the appropriate moieties in chromophore is strengthened and thereby the tendency to form a twisted intramolecular charge transfer state is increased [34].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, p ‐HBDI significantly loses fluorescence after it is stripped of the protein environment, because it decays mostly through cis ‐ trans photoisomerization in aprotic solvents via the S 1 /S 0 conical intersection at the torsional angle of 90° around the I‐bond . In protic solvents, it was suggested that solvent‐solute hydrogen bonding modifies the potential energy surface (PES) of the S 1 excited state in a way that the S 1 excited state decays through cis ‐ trans photoisomerization via the S 1 /S 0 conical intersection at the torsional angle smaller than 90° around the I‐bond . On the other hand, ab initio calculations at CASPT2//CASSCF level suggested the S 1 excited state of the p ‐HBDI anion decays mainly through barrierless torsional deformation around the P‐bond .…”
Section: Introductionmentioning
confidence: 99%
“…To explore or tune the photophysical properties of the GFP chromophore, chemists prepared p ‐HBDI and its various analogues. Thus, the cis ‐ o ‐ and cis ‐ p ‐ N , N ‐dimethylamino analogues ( cis ‐ p ‐DMABDI and cis ‐ o ‐DMABDI) of GFP chromophore were prepared for their possible interesting photophysical properties (Scheme ) . One of the interesting properties is, unlike the dual fluorescence of p ‐DMABN, they were reported to have single fluorescence, and their fluorescent emissions shift to higher wavelengths when they stay in a more polar solvent .…”
Section: Introductionmentioning
confidence: 99%